PEMANFAATAN MEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SEKOLAH DASAR - Afriza Muhammad Ikhsan; Amanda Kartika Widya Putri; Dindi Shifa Rohima Khairani; Tiara Himmatu Suroiya; Kholisotin Arnisa Ramadhani; Sahda Atika Ni’mah; Delia Indrawati; Hana Andriningrum (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the use of interactive learning media to improve the motivation and learning outcomes of elementary school students. The method used was a literature review of ten scientific articles published between 2022 and 2026, which were analyzed descriptively. The results indicate that interactive media such as multimedia, animated videos, and learning applications have a positive impact on student motivation, engagement, and understanding, as well as improving learning outcomes. However, their effectiveness is also influenced by teachers' learning strategies. Therefore, the use of interactive media requires appropriate planning to make learning more engaging and meaningful.